Ответы и объяснения

2013-12-22T07:01:44+00:00
1) 
sqrt(х+11) = х-1 

ОДЗ: x+11>=0 => x>=-11 

x+11 = (x-1)^2 
x+11 = x^2-2x+1 
x^2-3x-10=0 
x1=5, x2 = -2 

2) 
х^2 + х + 4 = 4 
х^2 + х = 0 
x(x+1)=0 
а) x = 0 
б) x+1=0 
x=-1 
Ответ: x1 = 0; x2 =-1 

3) 
sqrt(2х+1) - sqrt(x) =1 
возведем обе часи в квадрат 
(sqrt(2х+1) - sqrt(x))^2 =1 
(2x+1) - 2sqrt(x(2х+1)) + x = 1 
3x - 2sqrt(x(2х+1)) = 0 
2sqrt(x(2х+1)) = 3x 
возведем обе части в квадрат 
4x(2x+1)=9x^2 
8x^2+4x-9x^2 = 0 
-x^2+4x=0 
x^2-4x=0 
x(x-4)=0 
а) 
x=0 
б) 
x-4=0 
x=4 
Ответ: x1=0; x2=4
правильно
мы это в 6 классе изучали